Impact of sand mining on the changes of morphological and physical dynamics in Sa’dang River, Pinrang District, Indonesia - A Arsyad; Didi Rukmana; Darmawan Salman; Ilham Alimuddin (Journal of Degraded and Mining Lands Management, 2020)
The research aimed to investigate the morphological changes and physical dynamics conditions of the Sa’dang River associated with river sand mining activities. The research is expected to benefit the efforts of the management of sand mining in this area and enrich knowledge about the issues of river sand mining. The study was conducted in Sa’dang River sand mining area, which includes villages of Pincara, Massewwae and Mangki of Pinrang District in South Sulawesi Province, Indonesia. A field survey was conducted in October to December 2019 to see the condition of the river along with the mining activities that were taking place. Field data analysis was combined with google earth imagery data for 2006, 2014, 2017 and 2019 using ArcGIS 10.5 software to see changes in river morphology, formation and extent of point bar and channel bar, as well as changes in the area of river water bodies and non-water river bodies. The results showed that the changes in morphology and physical dynamics conditions of the Sa’dang River showed their own pattern. If sediment deposits forming point bars or channel bars were reduced, the area of river water bodies tended to increase. Or in other words, the width of the river is inversely proportional to the increase in the area of the river water body if the area of sediment deposits that form the point bar and channel bar tends to decrease.